Rising Power and Changing People The Australian High Commission in India - Lowe, David; Meadows, Eric (ANU Press, 2022)
Beginning in 1943-44, Australia's relationship with India is its oldest continuous formal diplomatic relationship with any Asian country. The early diplomatic exchanges between Australia and India have teased for their suggestions of potential unrealised, for opportunities missed, especially when compared with the very recent excitement about the future of Australia-India relations. How did Australia's representatives and their staff in New Delhi negotiate the many dimensions of Australia-India relations? This book brings together expert analyses of the work of the Australian High Commission, its key people and the challenges they faced in New Delhi. The important India Economic Strategy to 2035 report handed to the Australian Government in mid-2018 begins with the comment: 'Timing has always been a challenge in Australia's relationship with India.' As the Australian Government works to implement some of the ambitious recommendations in the report, this book adds to our understanding of why timing has been a challenge, and how those at the coalface of the relationship have grappled with it.